Distal phalanx desmoplastic fibroma of the hallux: a unique case mimicking a glomus tumor - Samy Ajarrag; Marie-Christine Torchon (BMC Musculoskeletal Disorders)
Abstract Background Desmoplastic fibroma is a rare, benign bone tumor that exhibits locally aggressive behavior and typically occurs in the mandible and long bones. Its presence in small bones, particularly in the hallux, is exceedingly rare. Desmoplastic fibroma’s unusual presentation in this region often mimics other lesions, such as glomus tumors, and poses significant diagnostic challenges. Case presentation We present the case of a 38-year-old female with a history of trauma to the affected toe and thyroid cancer, who experienced persistent subungual pain, localized tenderness, and cold hypersensitivity in the hallux. Initial imaging (X-ray and MRI) revealed findings consistent with a glomus tumor, including bone erosion in the distal phalanx. Surgical excision with wide margins was performed due to the patient’s cancer history, and histopathology unexpectedly identified the lesion as desmoplastic fibroma. The patient underwent regular follow-up with X-rays over two years, showing complete healing and no recurrence. Conclusions The case emphasizes the necessity of sending excised specimens for pathological analysis to confirm the diagnosis. Documenting such atypical presentations contributes valuable information to the limited literature on desmoplastic fibroma and aids clinicians in recognizing this rare tumor in unusual locations, potentially improving diagnostic accuracy and management.